Comparison of ISO and ASTM standards in determining the flexural strength of denture base resin - Venkat Sri̇ram; Venkatraman Jayaraman; N.gopi Chander (Istanbul University, 2019)
Purpose: The aim of this study was to compare the differences between the ASTM D790 and ISO 20795.1.2013 standards in evaluating the flexural strength of heat cure poly methyl methacrylate (PMMA) denture base resin. Materials and Methods: 30 heat cure denture base samples were fabricated in accordance to ISO 20795.1.2013 and ASTM D790 Standards. The specimens were finished and stored following the standardized protocol. The flexural strength was determined using universal testing machine at cross head speed of 1.50 mm/min and a span length of 40.00 mm. The mean flexural strength values were calculated in megapascals (MPa), and statistically analyzed. Results: The mean flexural strength of heat cure PMMA found with ISO and ASTM ranged between 60.492 MPa and 61.470 MPa. There was no significant difference between the two methods. Conclusion: The quantitative differences existed in the flexural strength of denture base resin between ISO 20795.1.2013and ASTM 790 protocols but those differences had no statistical and clinical significance.